Management Trends Towards Sustainable Environment: Nexus between CO2 Emissions, Natural Resource Depletion and Foreign Direct Investment - Bayahya, Wedyan Y.; Kayani, Farrukh Nawaz; Belhaj, Fozi Ali; Bayahya, Areej Y. (International Journal of Energy Economics and Policy, 2025)
Nowadays, environmental sustainability has become a major concern for the policymakers and researchers, therefore, this study investigated the effects of environmental sustainability factors which are CO2 emissions and Natural Resource Depletion on inward Foreign Direct Investment in Asian economies. The study used data Spanning from 1997 to 2022, and employed the panel data analysis, leveraging econometric models to capture both the short-run and the long-run impacts upon inward FDI. The findings revealed that CO2 emissions have significant negative impact upon FDI in the long run. In addition, it emphasized the importance of environmental concerns in investor decision-making. In contrast, Natural Resource Depletion showed a significant positive impact, highlighting the attraction of resource-dependent industries despite sustainability concerns. The study highlighted the necessity of sustainable policies to strike a balance between economic growth with environmental preservation, offering valuable insights for future research and policymakers.